The De-theologization of Religiosity: Heidegger’s Sin - Helenius, Timo S. (Ruch Filozoficzny, 2020)
It is hard not to agree with the thesis that Heidegger’s early work presented a distinct theological horizon that, in turn, provided a platform for the further development of phenomenology in Being and Time. In order to bring this existing discussion and widely shared scholarly conviction of Heidegger’s “de-theologization” of religiosity into contact with dogmatically expressed theological anthropology, the essay will explore Heidegger’s understanding of sin as expressed in his pre-Kehre texts. This essay will, therefore, focus on a selection of Heidegger’s analyses of “sin” from his 1920–1921 lecture course on the phenomenology of religion up to his 1927 lecture on “Phenomenology and Theology” as an exploration to the thought that finds its expression in Being and Time. Hence, this essay argues from its specific vantage point in a secondary fashion that Heidegger continued, beyond his early years in Freiburg and Marburg, to import theological insights into his own work. This proposal of the continued importance of theology in Heidegger’s work, albeit in a modified or in some ways de-theologized manner, is affirmed by Heidegger’s comments of it in Being and Time.